ARE CONSERVATIVISM AND CAPITALISM IN A FRIENDSHIP? Dušan Dostanić and Aleksandar Novaković, eds. 2022. Conservatism and Capitalism. An Unease Dialogue?. Belgrade: Institute for Political Studies, 135 p. - Ćurčić, Petar (Serbian political thought, 2024)
It is a review of the book: Dušan Dostanić and Aleksandar Novaković, eds. 2022. Conservatism and Capitalism. An Unease Dialogue?. Belgrade: Institute for Political Studies, 135 p.